Diagnostic Techniques and Surgical Management of Brain Tumors 2011
DOI: 10.5772/19788
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Photodynamic Diagnosis of Brain Tumors Using 5-Aminolevulinic Acid

Abstract: Diagnostic Techniques and Surgical Management of Brain Tumors 228 2. 5-ALA metabolic pathway 2.1 5-ALA metabolism in normal cells 5-ALA is a substance that naturally exists in the body. In the first stage, 5-Ala is produced via the condensation of glycine and succinyl-CoA by ALA synthetase (ALAS) in the mitochondria. This process receives negative feedback from heme, which is the endproduct. 5-ALA is actively transported via cytoplasm. In the next step, porphobilinogen (PBG) is created from ALA via ALA dehydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Almost all cases were positive (strong and vague) for 5-ALA-induced fluorescence. However, one study reported that 20% of PCNSL cases lacked 5-ALA-induced fluorescence (12). In the present case, we chose an open resective approach to the cerebellar tumor, without exposing the fourth ventricle, and observed strong 5-ALA-induced fluorescence of the tumor that was histologically compatible with DLBCL.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Almost all cases were positive (strong and vague) for 5-ALA-induced fluorescence. However, one study reported that 20% of PCNSL cases lacked 5-ALA-induced fluorescence (12). In the present case, we chose an open resective approach to the cerebellar tumor, without exposing the fourth ventricle, and observed strong 5-ALA-induced fluorescence of the tumor that was histologically compatible with DLBCL.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, 5-ALA has also been identified as a promising intraoperative marker in stereotaxic biopsies for malignant gliomas (5,15). However, clinical application of 5-ALA in primary central nervous system lymphoma (PCNSL) is currently uncommon (2, 8,12).…”
Section: Introductionmentioning
confidence: 99%
“…When 5-ALA is administered, the tumor cells take it up and synthesize heme actively. However, ferrochelatase, which is necessary for synthesis of heme from PPIX in the tumor cells, is relatively insufficient, and PPIX accumulates in tumor cells because, as a result, synthesis does not advance [3,6]. This PPIX may be found in surrounding tissues where no tumor cells exist [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, PPIX fluorescence is not observed in all tumors when 5-ALA is administered [3,4]. There is no method of ascertaining preoperatively whether PPIX fluorescence of the tumor tissue will be observed until exposure to an excitation light of the ultraviolet region during tumor resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation